Lipoprotein X : biochemical predictors and detection by non-denaturing polyacrylamide gradient gel electrophoresis - Le Riche, Mia (Stellenbosch : Stellenbosch University, 2011)
Assignment (MMed)--University of Stellenbosch, 2007.